Validity and reliability of instruments designed to measure factors influencing the overuse of antibiotics - Arwa Alumran; Xiang-Yu Hou; Cameron Hurst (Elsevier, 2012)
Background: Antibiotic overuse is a global public health issue that is influenced by several factors. The degree and prevalence of antibiotic overuse is difficult to measure directly. A more practical approach, such as the use of a psycho-social measurement instrument, might allow for the observation and assessment of patterns of antibiotic use. Study objective: The aim of this paper is to review the nature, validity, and reliability of measurement scales designed to measure factors associated with antibiotic misuse/overuse. Design: This study is descriptive and includes a systematic integration of the measurement scales used in the literature to measure factors associated with antibiotic misuse/overuse. The review included 70 international scientific publications from 1992 to 2010. Main results: Studies have presented scales to measure antibiotic misuse. However, the workup of these instruments is often not mentioned, or the scales are used with only early-phase validation, such as content or face validity. Other studies have discussed the reliability of these scales. However, the full validation process has not been discussed in any of the reviewed measurement scales. Conclusion: A reliable, fully validated measurement scale must be developed to assess the factors associated with the overuse of antibiotics. Identifying these factors will help to minimize the misuse of antibiotics. Keywords: Validity, Reliability, Measurement instrument, Antibiotics, Psycho-social factors